MICROBIOLOGICAL TEST OF SQUID (Loligo sp.) WET NOODLES DURING STORAGE - Anita Treisya Aristawati; Finarti Finarti; Hanifah Hanifah; Alismi M Salanggon; Roni Hermawan (Fakultas Perikanan dan Kelautan, Universitas Riau, 2021)
oodles are one of the favorite foods in the world. This is because the noodles in the presentation are quite easy and not difficult to serve, for example cooking instant noodles is quite easy to only brew for 3-4 minutes with boiling water. In the market, generally wet noodles in circulation can only last for approximately 2 to 3 days at room temperature. This is because wet noodles have a fairly high water content. In a food, the water content is high enough, it can trigger the growth of microorganisms. Wet noodles damage can be caused by S. aureus, E. coli, mesophyll bacteria and molds. The purpose of this study was to determine the microbiological quality of squid wet noodlesduring storage. Microbiological testing of wet noodles was carried out with five kinds of tests, namely Total Plate Number (ALT), Most Probable Number (MPN), Test on Salmonella spp. bacteria, Test on S. aureus bacteria, and Yeast Mold Rates. This study used 3 (three) treatments and 5 replications. The results showed that storage time affected the microbiological quality of cooked squid wet noodles, where the quality of wet noodles could still last up to 24 hours of storage.